Corrosion surface morphology-based methodology for fatigue assessment of offshore welded structures - Okenyi, Victor; Afazov, Shukri; Mansfield, Neil; Eder, Martin Alexander; Abrahamsen, Asger Bech; Fæster, Søren; Klingaa, Christopher Gottlieb; Siegkas, Petros; Bodaghi, Mahdi (My University, 2023)
This work employed a novel corrosion-based fatigue model to determine the fatigue life of offshore welded structures to enable the fatigue assessment of welds under corrosive conditions. In addition to the material's ultimate strength, endurance limit, and stress ratio (mean stress effect), the model includes a corrosion factor concept to account for the impact of corrosion pits on the fatigue performance of welded S355 steel, which is the novel contribution in this paper. X-ray computed tomography scans of corroded S355 specimens in a salt spray chamber were characterized. Surface texture characterization was employed to obtain surface roughness, size, and aspect ratio of corrosion pits. The corrosion factor was determined based on notch and surface fatigue theories using the characterized pit size, aspect ratio, and surface roughness. Fatigue S-N curves were then predicted for critical pits and compared against the fatigue code DNVGL-RP-C203 and experimental data from the literature. The novel approach combining corrosion characterization method with corrosion-based fatigue model for the prediction of fatigue S-N curves provided a minor deviation of only 2.8% between predicted and measured data. This approach can potentially be integrated into predictive frameworks for the remaining life assessment of offshore structures.
Keywords: Corrosion characterization; Corrosion pits; Corrosion-based fatigue model; Endurance limit; Fatigue notch theory; Fatigue surface theory; S355 S-N curves; Stress concentration; Surface roughness; X-ray computed tomography